Post-medieval stelae cemetery in Nowy Dwór: preliminary results of an anthropological and archaeological study - Lepionka, Hubert; Słodka, Angelika; Dec, Olga (Anthropological Review, 2022)
The paper presents preliminary results of an anthropological analysis of a previously unknown post-medieval stelae cemetery in the village of Nowy Dwór in Podlaskie Voivodeship, Poland. The main aim of the study was to identify the site itself, and to create the probable biological profile of the local population. The research confirmed the existence of a post-medieval necropolis in which remains of at least 181 individuals were unearthed, with 111 individuals discovered in 88 intact graves and their closest proximity. Few individuals were equipped with what can be interpreted as “obol of the dead”, and at least three burials could be classified as deviant. Biological analysis showed that 33% of analysed individuals regardless of age bore infection-related lesions and post inflammatory pathologies. Constructed mortality tables also correspond more with tables for medieval rather than post-medieval populations. As a conclusion, collected evidence and results of analysis seem to verify the historical accounts mentioning several plague outbreaks in the region, occurring from the 16th to 18th centuries. Individual findings such as “obol of the dead”, as well as the “deviant grave”, likely belonging to a whisperer (witch), can also provide useful to further research on local traditions and beliefs.